Vitamin D and Metabolic Dysfunction-Associated Fatty Liver Disease (MAFLD): An Update - Barchetta, Ilaria (Nutrients, 2020)
Non-alcoholic fatty liver disease (NAFLD) is the first cause of chronic liver disease worldwide; it ranges from simple steatosis to steatohepatitis (NASH) and, potentially, cirrhosis and hepatocarcinoma. NAFLD is also an independent risk factor for type 2 diabetes, cardiovascular diseases, and mortality. As it is largely associated with insulin resistance and related disorders, NAFLD has been recently re-named as Metabolic dysfunction-Associated Fatty Liver Disease (MAFLD). At present, there are no approved pharmacological treatments for this condition. Vitamin D is a molecule with extensive anti-fibrotic, anti-inflammatory, and insulin-sensitizing properties, which have been proven also in hepatic cells and is involved in immune-metabolic pathways within the gut–adipose tissue–liver axis. Epidemiological data support a relationship hypovitaminosis D and the presence of NAFLD and steatohepatitis (NASH); however, results from vitamin D supplementation trials on liver outcomes are controversial. This narrative review provides an overview of the latest evidence on pathophysiological pathways connecting vitamin D to NAFLD, with emphasis on the effects of vitamin D treatment in MAFLD by a nonsystematic literature review of PubMed published clinical trials. This article conforms to the Scale for Assessment of Narrative Review Articles (SANRA) guidelines. Evidence so far available supports the hypothesis of potential benefits of vitamin D supplementation in selected populations of NAFLD patients, as those with shorter disease duration and mild to moderate liver damage.